A135 HEMORRHAGIC CNS INFARCT AS A MANIFESTATION OF ULCERATIVE COLITIS WITH LIVER CIRRHOSIS IN AN ADOLESCANT BOY. (15th March 2019) - Al Yarubi, Z; Schreiber, R; Sargent, M
Abstract: Background: Hemorrhagic strokes in children have an annual incidence of 1.1 per 100, 000 accounting for 50% of strokes with vascular malformations being the most common cause. Adult patients with liver cirrhosis are at increased risk for CNS infarct. While IBD patients also have an increased risk of thrombotic events with deep vein thrombosis and pulmonary embolism being most common, CNS thrombotic events are much less common ranging from 1.3% to 7.5% of adult cases versus 0.67 per 100 000 pediatric cases. Aims: To present an adolescent case of UC and cirrhosis with hemorrhagic stroke and to provide a review of the literature on this subject. Methods: Patient chart review was conducted. A literature review using Google Chrome and PubMed with search keywords for intracranial hemorrhage and hemorrhagic stroke with liver disease or cirrhosis and IBD in adults and children. Results: A 17 year old boy with UC in remission on azathipoprine and well-compensated cirrhosis secondary to autoimmune sclerosing cholangitis presented with sudden onset left arm weakness and facial droop. Investigaitons showed Hb of 99 g/L, PLT 76 x 10 9 /L, Urea: 2 mmol/L, AST 174 U/L, ALT 630 U/L, GGT 52 U/L, INR 1.3, PTT: 24 sec, PT: 12.7 sec and Fibrinogen 1.8 g/L (n). Head CT scan showed an acute hemorrhage in the posterior right frontal lobe measuring 2.4 x 1.4 x 2.9 cm with mild surrounding edema. A CT angiogram did not identify any vascular malformations or aneurysms. He received vitamin K and platelets and was managed conservatively. By discharge, he had improved power in his left arm. In our literature review, a US retrospective cohort study found an increased risk of stroke in adults with cirrhosis versus non liver disease patients. In contrast a Taiwan study on intracerebral hemorrhage found no difference in the frequency between cirrhotic and patients with no liver disease (1.3 % versus 1%). Patients with non alcoholic fatty liver disease are reported to be at increased risk for stroke. Pediatric patients with Alagille syndrome also have an increased risk for intracranial bleed due to vascular anomalies. However, no cases of intracerebral bleed was reported in pediatric or adolescent patients with IBD and liver cirrhosis. Conclusions: This is the first reported case of an adolescent with UC and cirrhosis presenting with hemorrhagic infarct. While individuals with cirrhosis may be at increased risk for thrombotic CNS infarct, it is uncertain if they have an increased risk for hemorrhagic infarcts. Similarly, although IBD is known to increase risk for thrombotic events including CNS infarcts, intracranial hemorrhage is unusual. Funding Agencies: None